(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2023)
While hospitality and Tourism education is relatively new to the country, it is being recognized as vital for the growth of the industry. Thus, drawing on quantative data gathered from Advanced Level Accommodation Operations students (Batch no.237) at Sri Lanka Institute of Tourism and Hotel Management (SLITHM), this research paper sheds light on their perceptions of significant challenges facing contemporary Hospitality and Tourism education. These include: engaging contemporary students particularly through new technologies; resource pressures and the distinctiveness of hospitality management education; ongoing tensions between hospitality’s intellectual development and its practice focus; and new course structures, delivery modes and partnerships. The study also investigates their views on how those are likely to expand in the future. The purpose of this research was to redefine these challenges and find innovation keys to mitigate those challenges for revamping Hospitality and Tourism education. Self-designed 04 questionnaires and 02 interviews were utilized to collect data from all the 25 Accommodation Operations students. The students’ responses were carefully analyzed and evaluated to find the reasons for the challenges. The main reasons were the less exposure to the Hospitality and Tourism industry and new technology, lack of leadership skills, internationalization, innovative teaching methodologies and simulation activities. Hence field trips, experiential learning, personality and leadership development workshops, trainings for online learning and introduced overseas programmes in the pursuit of internationalization as strategies for diversity in Hospitality and Tourism education which yielded favourable results. According to the results of this research it is highly recommended that the curriculum might be improved by creating modules of related courses, applying a cross-disciplinary approach to studies, using corresponding teaching-learning methods and creating a supportive learning environment, initiating autonomous learning for the students and motivating them for studies for a seismic shift.